Preparation For Abroad Graduates To Return Home: Case Study at Wageningen University And Research Holland - Hadi, Cecilia Valentina Sri (Jurnal Abdimas Dedikasi Kesatuan, 2025)
The importance of preparing for diploma equivalency for graduates of state universities is one of the things that graduates need to think about while they are still studying abroad. Online input techniques make it necessary to prepare complete documents so that the process runs smoothly. Keywords: diploma, equivalency, Overseas education